Eosinophil-specific deletion of I?B? in mice reveals a critical role of NF-?B-induced Bcl-xL for inhibition of apoptosis - Schwartz, Christian; Willebrand, Ralf; Huber, Silke; Rupec, Rudolf A.; Wu, Davina; Locksley, Richard; Vöhringer, David (Blood, 2015)
Eosinophils are associated with type 2 immune responses to allergens and helminths. They release various proinflammatory mediators and toxic proteins on activation and are therefore considered proinflammatory effector cells. Eosinophilia is promoted by the cytokines interleukin (IL)-3, IL-5, and granulocyte macrophage-colony-stimulating factor (GM-CSF) and can result from enhanced de novo production or reduced apoptosis. In this study, we show that only IL-5 induces differentiation of eosinophils from bone marrow precursors, whereas IL-5, GM-CSF, and to a lesser extent IL-3 promote survival of mature eosinophils. The receptors for these cytokines use the common ? chain, which serves as the main signaling unit linked to signal transducer and activator of transcription 5, p38 mitogen-activated protein kinase, and nuclear factor (NF)-?B pathways. Inhibition of NF-?B induced apoptosis of in vitro cultured eosinophils. Selective deletion of I?B? in vivo resulted in enhanced expression of Bcl-xL and reduced apoptosis during helminth infection. Retroviral overexpression of Bcl-xL promoted survival, whereas pharmacologic inhibition of Bcl-xL in murine or human eosinophils induced rapid apoptosis. These results suggest that therapeutic strategies targeting Bcl-xL in eosinophils could improve health conditions in allergic inflammatory diseases.
EVALuna2:25866